Special educational needs of students with autism spectrum disorders - Khaustov, A.V. (Autizm i narušenie razvitiâ, 2016)
Education of children with autism spectrum disorders is possible only if their special educational needs are taken into account. Special educational needs of children form the demand for special educational conditions. On the basis of the existing primary list of special educational needs in the approximate adapted basic general education program for students with autism spectrum disorders and with consideration of contemporary sci¬entific data about particularities of their development the structured list of 4 groups of basic educational needs was made. The first group of educational needs is the special organization of the educational process, the sec¬ond — with the adaptation of the content of the educational program, the third — with adaptation of presenta¬tion of learning material, the fourth — with overcoming hardships in development, social skills and adaptation. Образование детей с расстройствами аутистического спектра возможно только с учетом их особых образовательных потребностей. Особые образовательные потребности детей обуславливают необходимость создания специальных образовательных условий. На основе существующего первоначального перечня особых образовательных потребностей, представленного в примерной адаптированной основной общеобразовательной программе для обучающихся с расстройствами аутистического спектра, и с учетом современных научных данных об особенностях их развития выделен структурированный перечень 4-х групп особых образовательных потребностей. Первая группа образовательных потребностей связана с особой организацией образовательного процесса, вторая группа — с адаптацией содержания образовательной программы, третья — с адаптацией способов подачи учебного материала, четвертая группа — с преодолением трудностей в развитии, социализации и адаптации.